Brachionidae (Rotifera: Monogononta) de la albufera El Paraíso y el reporte de Brachionus ibericusen el Perú - Toscano, Emily (2013)
This paper reports the Brachionidae species recognized in samples collected in October 2010 in the albufera Laguna El Paraiso, Huacho (11°13’ −11°10'S , 77°35' −77°40'W). Five species were determined: Keratella tropica, Brachionus quadridentatus, B. urceolaris, B. angularis and B. ibericusCiros-Pérez 2001, which is a new report for Peru and this report expanding its worldwide distribution.